Perempuan Pedagang dan Pasar Tradisional - Danik Fujiati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
the traditional market are identically with women, because in any traditional market, especially in Indonesia as much as 85% of trades are dominated by women, even buyers in traditional markets are mostly (90%) also women and of course the merchandise being sold is also related to women or identical with domestic needs. These conditions make women (traders) have economic power and dominate the flow of trade, ranging from the determination of the price of goods, capital, produc relations and division of labor, even determinants of social and cultural relations that exist in traditional markets. Women traders as key actors who have power and dominance in traditional markets, must be central in building patterns of relationships with various other subjects, who play a role in the market. For example: with husbands, with other traders, with buyers, with owners of capital, with suppliers of goods, with porters and laborers carrying. Relationship patterns built by women traders with these subjects, some involving gender sentiments and some that are not, there are a vertical relationship and there are a horizontal relationship.